AMERICAN POLITICAL SATIRES TOWARD OBAMA’S PRESIDENTIAL CHAMPAIGN AS REFLECTED IN JIBJAB.COM’S ANIMATED CARICATURES - Didik Murwantono (Universitas Stikubank (UNISBANK) Semarang, 2012)
This paper is intended to reveal political satires in the American media, mainly it reflects in JibJab.com’s animated caricatures on the concentration of Obama’s Presidential Champaign. It is also to discern the deep meaning of the satirical drawing in Obama’s presidential election and to disclose how satire takes a part in Obama’s campaign. Politics, social, and culture are to be prominent disciplines associated with the phenomenon of animated caricatures of Obama’s presidential campaign. There are three functions of satirical drawing in American politics as follows: satirical animated caricature as the symbolic interaction, satirical drawing as the social control, and satirical caricature as the political correctness. Some significant values are also correlated with the political caricatures such as freedom of expression, democratic values, and the equality values. This analysis describes the contribution of the political satires in the time of Obama’s presidential election, used as tools for campaign, and tools to influence the voters. Key words: caricature, political satire, Obama’s presidential election, JibJab.com